2010
DOI: 10.1521/suli.2010.40.4.394
|View full text |Cite
|
Sign up to set email alerts
|

Awareness Effects of a Youth Suicide Prevention Media Campaign in Louisiana

Abstract: Research on the efficacy of mediated suicide awareness campaigns is limited. The impacts of a state-wide media campaign on call volumes to a national hotline were analyzed to determine if the advertisements have raised awareness of the hotline. We use a quasi-experimental design to compare call volumes from ZIP codes where and when the campaign is active with those where and when the campaign is not active. Multilevel model estimates suggest that the campaign appears to have significantly and substantially inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
2
25
0
1
Order By: Relevance
“…The findings are more divergent when behavioral outcomes are considered. Some studies have found that media campaigns can boost help-seeking (Bossarte et al, 2014;Jenner et al, 2010;Oliver et al, 2008) whereas others suggest that they make no difference or only have an impact when particular sources of help or particular types of help-seeking are considered (Daigle et al, 2006;Till et al, 2013). Relatively few studies have had sufficient statistical power to examine whether media campaigns impact on the ultimate behavioral outcome of number of suicides, but the studies that were adequately powered demonstrated significant reductions (Matsubayashi et al, 2014;Mishara & Martin, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings are more divergent when behavioral outcomes are considered. Some studies have found that media campaigns can boost help-seeking (Bossarte et al, 2014;Jenner et al, 2010;Oliver et al, 2008) whereas others suggest that they make no difference or only have an impact when particular sources of help or particular types of help-seeking are considered (Daigle et al, 2006;Till et al, 2013). Relatively few studies have had sufficient statistical power to examine whether media campaigns impact on the ultimate behavioral outcome of number of suicides, but the studies that were adequately powered demonstrated significant reductions (Matsubayashi et al, 2014;Mishara & Martin, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Bossarte et al (2014) found there were significant increases in the average numbers of calls over the campaign period in six cities exposed to the campaign but not in the four comparison cities. After adjusting for seasonal fluctuations in calls, Jenner, Jenner, Matthews-Sterling, Burrs, and Williams (2010) found that the average daily number of calls to helplines significantly increased in parishes exposed to the campaign but not in the unexposed ones. Till, Sonneck, Baldauf, Steiner, and Niederkrotenthaler (2013) observed that the overall number of helpline calls was significantly higher in the three months of the campaign than in the three months prior to the campaign in the intervention region but not in a comparison region, but that this mirrored seasonal trends.…”
Section: Studies Using Pre-and Post-campaign Data With Additional Timentioning
confidence: 98%
“…6 Previous studies on mental health awareness campaigns for issues of suicide and depression showed modest effects on attitudes and knowledge of causes and treatments, and slight or no detectable effects on behavioural outcomes. [9][10][11][12][13] The studies showed high subject attrition rates, low response rates and small samples, and/or were based on statistical techniques that were unable to adjust for underlying trends, such as uncontrolled before-and-after evaluation or time series data with too few observations. 9-13 Our study findings were based on time series data with a 24-month post-campaign study period and adjustment for secular trends and data seasonality.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Studies evaluating the effect of mass media interventions aimed at reducing stigma have focused on knowledge, attitude and behavioural intentions as outcome measures. 6,[8][9][10][11][12][13] These outcomes are assumed to be consistent with actual behaviour when the behaviour is not directly assessed. 5 Destigmatization may lead to increased readiness to seek professional help; however, few studies have examined the impact of stigma on actual help-seeking behaviour.…”
mentioning
confidence: 99%
“…Some of these are before-and-after studies of entire campaigns that assess changes in community-level indicators related to suicide (e.g., suicide rates and calls to helplines) (Jenner, Jenner, Matthews-Sterling, Butts, & Williams, 2010;Matsubayashi, Ueda, & Sawada, 2014;Oliver et al, 2008;Till, Sonneck, Baldauf, Steiner, & Niederkrotenthaler, 2013) and just two have been randomized control trials (RCTs) (Klimes-Dougan & Lee, 2010;Klimes-Dougan, Yuan, Lee, & Houri, 2009). The available evidence from the before-and-after studies indicate that suicide prevention campaigns are associated with an increase in the number of calls to helplines (Jenner et al, 2010;Oliver et al, 2008;Till et al, 2013) and a decrease in the number of suicides in subsequent months (Matsubayashi et al, 2014). The two RCTs exposed participants to a simulated billboard advertisement, a simulated television advertisement and a 'no information' condition.…”
Section: Introductionmentioning
confidence: 99%